Utilização de enzimas em dietas para suínos - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Swine production is very importat in the southern region of the country, produces jobs, profits ond produces animal protein, very produced in the world and the country. However, with this great production, at a fast pace, there are a few problems, one of them being the pollution caused by manure of animals, which has been increasing significantly in recent years, due to the large volume of pig production in areas often small. . In order to overcome this problem has been intensified the use of enzymes, which aim at improving the use of the diet ingested, because some essential nutrients aren’t used by animals for they don’t produce the enzyme necessary for its metabolism. Among the enzymes more important pig stands out the phytase, because the pigs not to produce and therefore cann’t take advantage of the phosphorus that isn’t available in the diet. With the supplementation of this enzyme the utilization of phosphorus ingested will be higher, thus reducing the phosphorus removed by manure and with this, your potential polluter, reducing contamination of water and soil. The best utilization of food also influence on the reduction of costs, but the use of enzymes in diets generates costs, and the cost-benefit is not often discussed, making great part of publications on the subject incomplete.
Keywords: Dejetos; Fitase; Nutrição; Suinocultura; Phytase; Manure; Nutrition; Swine production; CNPQ::CIENCIAS AGRARIAS